Purpura Henoch Schonlein pada Perempuan Dewasa - Daniel Matius (PT Kalbe Farma Tbk., 2020)
Vaskulitis IgA/Purpura Henoch Schonlein adalah peradangan sistemik pembuluh darah kecil; umumnya menyerang anak-anak usia 2-5 tahun; ditandai dengan bercak merah pada kulit disertai gejala sendi, gastrointestinal, dan ginjal. Dilaporkan kasus wanita dewasa dengan Purpura Henoch Schonlein. Vaskulitis IgA / Henoch Schonlein Purpura is a systemic inflammatory disease of small blood vessels characterized by the appearance of reddish patches on the feet. This disease generally affects children aged 2 - 5 years, characterized by skin red spots accompanied by symptoms in the joints, gastrointestinal, and kidney disorders. This is a case of adult woman with Henoch Schonlein Purpura.